Fentanyl and Propofol Used at The Conclusion of Anesthesia in Pediatrics Patients to Reduce Emerging Anxiety Following Sevoflurane Anesthesia: A Comparative Study in Libyan Patients (Journal of Academic Research, 2024)
Background: The optimal drug for reducing emergence agitation (EA) after sevoflurane anesthesia remains unclear, with both propofol and fentanyl as potential options.Aim: This study aimed to compare the effects of fentanyl and propofol on the incidence and severity of postoperative agitation and excitement following sevoflurane anesthesia.Methods: Sixty-six children who underwent sevoflurane anesthesia were prospectively assigned to three groups. Group P received propofol 1 mg/kg, Group F received fentanyl 1 μg/kg, and Group S received saline. EA was assessed using the Pediatric Anesthesia Emergence Delirium (PAED) scale, alongside recovery time and the occurrence of nausea and vomiting.Results: Group P and Group F had mean PAED scores of 5.05 and 5.2, respectively (p=0.715), significantly lower than Group S (14, p